Transcriptomic changes across the life cycle of Trypanosoma cruzi II - Cruz-Saavedra,Lissa; Vallejo,Gustavo A.; Guhl,Felipe; Ramírez,Juan David (PeerJ, 2020)
Trypanosoma cruzi is a flagellated protozoan that causes Chagas disease; it presents a complex life cycle comprising four morphological stages: epimastigote (EP), metacyclic trypomastigote (MT), cell-derived trypomastigote (CDT) and amastigote (AM). Previous transcriptomic studies on three stages (EPs, CDTs and AMs) have demonstrated differences in gene expressions among them; however, to the best of our knowledge, no studies have reported on gene expressions in MTs. Therefore, the present study compared differentially expressed genes (DEGs), and signaling pathway reconstruction in EPs, MTs, AMs and CDTs. The results revealed differences in gene expressions in the stages evaluated; these differences were greater between MTs and AMs-PTs. The signaling pathway that presented the highest number of DEGs in all the stages was associated with ribosomes protein profiles, whereas the other related pathways activated were processes related to energy metabolism from glucose, amino acid metabolism, or RNA regulation. However, the role of autophagy in the entire life cycle of T. cruzi and the presence of processes such as meiosis and homologous recombination in MTs (where the expressions of SPO11 and Rad51 plays a role) are crucial. These findings represent an important step towards the full understanding of the molecular basis during the life cycle of T. cruzi.
Keywords: Trypanosoma cruzi; Metacyclic trypomastigotes; Epimastigotes; Trypomastigotes; Transcriptomic; Pathways